International intervention : sovereignty versus responsibility - Keren, Michael; Sylvan, Donald A. (F. Cass, 2002)
National sovereignty, defined as a nation's right to exercise its own law and practise over its territory, is a cherished norm in the modern era, and yet it raises great legal, political and ethical dilemmas. This study looks at the problems created by international intervention.